An analysis of preschool teachers’ sense of efficacy: A case of TRNC - TORAN, MEHMET (My University, 2017)
Determining the factors that affect teachers' competences has a decisive role in revealing the quality of teaching process. In this context, it is important to identify professional variables affecting the self-efficacy of preschool teachers. For this reason, it is aimed to investigate which professional variables influence preschool teachers' sense of efficacy. In the research, a descriptive research model was adopted. The working group of the study is composed of 191 preschool teachers participating in public nurseries and kindergartens in the TRNC, and also those participating to the research as a volunteer. The Professional Information Form and the Teacher’s Sense of Efficacy Scale were used as data collection tools in the study. Statistical analyses suitable for the analysis of the data were applied by applying the normality tests to the collected data. According to the findings obtained from the analysis made, except for the school type the preschool teachers graduated and the number of children, factors such as the graduated department, the place of residence, the duration of professional experience, the economic competence, and the educational environment were found to affect the self-efficacy of preschool teachers. As a result, it can be said that preschool teachers' self-efficacy is influenced by professional variables.
Keywords: Preschool; Preschool Teaching; Self-Efficacy; Teaching Strategies; Classroom Management; Sstudent Participation